Uma análise cinematográfica da película Árvores da Paz (2022) - Naiara Morena Roque Arcas (2024)
The feature film “Trees of Peace” (2022) is an independent production by Alanna Brown that narrates the daily lives of four women from the Hutu, Tutsi and American ethnicities (Annick, Jeanette, Mutesi and Peyton). The protagonists spent around 80 days in a small hideout in order to survive the Rwandan Genocide (1994). The european domination intensified the ethnic distinction and hostility between the Hutu and Tutsi ethnicities, leading to the Rwanda Genocide and it is estimated that in a period of 100 days, the Hutu ethnic group murdered around 660 thousand Tutsis (Melvern, 2020; Silva, 2020). The film “Trees of Peace” (2022) brings a female perspective and stars women who are often marginalized in historical narratives. Furthermore, the film explores the female experience and the implications of ethnic nationalism in the context of war. In this sense, we seek to understand how gender and ethnic nationalism are represented in “Trees of Peace” (2022)? To answer this question, we aimed to identify and analyze aspects of gender and ethnic nationalism in the cinematographic narrative of “Trees of Peace” (2022) under the aegis of postmodernism. We carried out a film analysis of the cut defined by meta-analysis and systematic methods. The results indicate that by acknowledging each other's stories, Anick, Jeanette, Mutesi and Peyton collaborate to dismantle the metanarratives associated with female identity, ethnic nationality and the single religion. Furthermore, we noticed that the ludic and the empathy played essential roles in the survival and maintenance of the protagonists’ mental health. Keywords: “Trees of Peace” (2022); Gender; Ethnic Nationalism; Postmodernism.